PLEISTOCENE LANG TRANG FAUNA IN NORTH VIETNAM: TAXONOMIC COMPOSITION AND HABITATS - A. V., Lopatin; E. N., Maschenko; Le, Xuan Dac; Dang, Ngoc Huyen; Pham, Mai Phuong; P. Yu. , Parkhaev; E. V. , Syromyatnikova (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Pleistocene Lang Trang Fauna in North Vietnam: Taxonomic Composition and HABITATSNew data on the taxonomic composition and ecological characteristics of Late Pleistocene vertebrates and invertebrates from the Lang Trang cave in northern Vietnam are presented. Based on the materials collected in progress of the work of the Joint Vietnam - Russia Tropical Science and Technology Research Center in 2020-2022, various representatives of the Stegodon-Ailuropoda Fauna of the second half of the Middle - early Late Pleistocene of Southeast Asia were identified, including primates Gigantopithecus blacki, Pongo sp., Trachypithecus sp., Presbytis sp., Macaca nemestrina, M. cf. fascicularis, M. cf. mulatta, and Macaca sp., carnivorans Panthera tigris, Neofelis nebulosa, and Arctonyx collaris rostratus, a lipotyphlan Chodsigoa hoffmanni, a bat Ia io, rodents Hystrix kiangsenensis, Leopoldamys neilli, and Rattus rattus, proboscideans Stegodon sp. and Elephas maximus, perissodactyls Tapirus indicus, Dicerorhinus sumatrensis, Rhinoceros sondaicus, and Rh. unicornis, artiodactyls Sus scrofa, S. barbatus, Tragulus kanchil, Hydropotes inermis, Muntiacus muntjak, Axis porcinus, Rusa unicolor, Capricornis sumatraensis, Bubalus arnee, and Bos sp., a crocodile Crocodylus sp., a turtle Cuora sp. and an abundant gastropod association, presented by six terrestrial forms, two freshwater species and a coastal-marine species Ellobium aurismidae. Gigantopithecus blacki, Macaca cf. fascicularis, M. cf. mulatta, Neofelis nebulosa, Chodsigoa hoffmanni, Ia io, Leopoldamys neilli, Rattus rattus, Rhinoceros unicornis, Sus barbatus, Tragulus kanchil, Hydropotes inermis, Axis porcinus, crocodiles, turtles, and most of gastropod species were identified for the first time in the Lang Trang Fauna based on these studies. Of particular interest is the finding of the giant ape G. blacki, one of the latest in the fossil record. The habitats of the fauna are characterized as mosaic biotopes with a predominance of wet stations and the participation of mangrove swamps and coastal lowlands; these conditions could have existed in the area of the cave during a major marine transgression of the early Late Pleistocene.